Regulation of Multidrug Resistance P‐Glycoprotein in the Developing Blood–Brain Barrier: Interplay between Glucocorticoids and Cytokines. (27th March 2016) - Iqbal, M.; Baello, S.; Javam, M.; Audette, M. C.; Gibb, W.; Matthews, S. G.
Abstract : P‐glycoprotein (P‐gp) encoded by Abcb1 provides protection to the developing brain from xenobiotics. P‐gp in brain endothelial cells (BECs) derived from the developing brain microvasculature is up‐regulated by glucocorticoids and inhibited by pro‐inflammatory cytokines in vitro . However, little is known about how prenatal maternal glucocorticoid treatment can affect Abcb1 /P‐gp function and subsequent cytokine regulation in foetal BECs. We hypothesised that glucocorticoid exposure increases Abcb1 /P‐gp in the foetal brain microvasculature and enhances the sensitivity of Abcb1 /P‐gp in BECs to the inhibitory effects of cytokines. BECs isolated from dexamethasone‐ or vehicle‐exposed foetal guinea pigs were cultured and treated with interleukin‐1β, interleukin‐6 or tumour necrosis factor‐α, and Abcb1 /P‐gp expression and function were assessed. Prenatal dexamethasone exposure significantly increased Abcb1 /P‐gp expression/activity and cytokine receptor levels in BECs of the foetal brain microvasculature. Foetal dexamethasone exposure in vivo also increased the subsequent responsiveness of BECs to pro‐inflammatory cytokines in vitro . In conclusion, maternal treatment with synthetic glucocorticoids appears to prematurely mature P‐gp mediated drug resistance at the foetal BBB in vivo and profoundly impact the subsequent responsiveness of P‐gp to pro‐inflammatory cytokines in the foetal BEC. The significance of these findings to foetal brain protection against xenobiotics and other P‐gp substrates in vivo requires further elaboration. However, the results of the present study may have implications for human pregnancy and foetal brain protection, particularly in cases of preterm birth combined with infection.